The Influence of Health Education Towards Buzz Group Method On Pregnant Women Knowledge About COVID-19 Pandemic at the Jember - Septiyono, Eka Afdi (Universitas Negeri Gorontalo, 2024)
Background: Coronavirus disease (COVID-19) is an infected disease which caused by Sars-Cov-2 and it also called with pneumonia virus this disease are spreads quickly in the worldwide. Pregnant women are being a vulnerable group for this disease. They have a lack of immune system that impacts a physiological systems. Buzz Group is one of the effective method for increasing knowledge. Objective: The aim of this study is analyzed the effect of health education with Buzz Group method to increase the pregnant woman knowledge about COVID-19 pandemic in the work area of Panti Public Health Center. Methods: This study used Quasy-experimental method with pre-post test and used a control group design. The research sample technique used purposive sampling, consist of 20 pregnant women in the intervention group and 20 pregnant women in the control group. Results: This study analyzed with Wilcoxon's test, the result showed that there is a significant effects of health education with buzz group method on pregnant women knowledge about the COVID-19 pandemic (p value = 0.0001). The study analyzed with Mann Whitney's test, the results showed that there is a significant difference in the effects of buzz group method on intervention and control group (p value = 0.042). Conclusion: Based on these, the buzz group method can be used as one of the granting health education to increasing knowledge.